A prospective cross-sectional study on epidemiological determinants, vaccine hesitancy and adverse events following anti rabies vaccination in an animal bite - Kaware, Alka; Pothipogu, Tejaswi; Ingle, Prachi; Deshmukh, Jyostna (International Journal Of Community Medicine And Public Health, 2024)
Background: Rabies is an infectious disease with hundred percent mortality that can be prevented by taking action pre or post exposure to the agent. The individuals’ beliefs, customs and traditions play a major role in any health care practices. In this study we tried to assess the epidemiological determinants, vaccine hesitancy and adverse events following vaccination. Objectives were to study the epidemiological determinants of the individuals with animal bite and to study the vaccine hesitancy and adverse events following vaccination. Methods: A prospective cross-sectional study was conducted among the 300 individuals who came with animal bite to the anti-rabies vaccination centre. The study participants were recruited through convenience sampling. Results: Out of 300 participants 102 (34%) were of age group 15-35 years. Males 188 (62.7%) and females 112 (37.3%). The common animal that reported to bite was dog which was seen in 85.7% of study population. Vaccine hesitancy was observed in 16.7% (50). The 83% (249) participants took the ARV vaccination within 24 hours of the animal bite. The most common adverse events following vaccination reported is skin discoloration at the injection site by 53.3% (160). Conclusions: The vaccine should be made available even in the rural, suburban areas. Newer vaccine with better preservatives should be made to prevent adverse events.